Language Effects in Second Language Learners: A Longitudinal ERP Study (Tufts Archival Research Center, 2005)
Are the mechanisms involved in word recognition in early L2 learners different from those of more proficient L2 users and how do these mechanisms evolve during learning? Our study sought to closely track language effects in beginning learners of an L2. In the present study both behavioral and ERP data were collected to investigate the changes over time of L2 processing in beginning learners. Monolingual L1 English-speakers enrolled in introductory Spanish at Tufts University were first trained on a list of 228 Spanish words and their English translations. These critical items were chosen from the vocabulary to be learned in their introductory Spanish class over the course of the semester. Behavioral data from this training session and the following experimental sessions showed expected learning effects. In the three subsequent experimental sessions the participants saw three lists - an English list, a Spanish list, and a mixed language list, performing a go/no-go lexical decision task. As observed in previous studies our results showed overall larger negativities in the N400 epoch to L1 items than to L2 items. The differences varied in that amplitudes in the traditional N400 epoch to L2 items became more negative over the course of the semester. These results suggest that L2 items become more connected in the mental lexicon rapidly in the earliest stages of learning a second language, emphasizing the plasticity of the mature brain.